Hospitalizations of Children with Huntington's Disease in the United States. Issue 5 (11th September 2017) - Mendizabal, Adys; Ngo Vu, Anh‐Thu; Thibault, Dylan; Gonzalez‐Alegre, Pedro; Willis, Allison
Abstract: Background: Juvenile Huntington's disease (JHD) is a childhood‐onset neurodegenerative disorder. Although it is caused by the same pathologic expansion of CGA repeats as adult‐onset Huntington's disease, JHD has distinct clinical features. Most clinical research in HD focuses in the adult‐onset disease; therefore, little is known about acute care outcomes for patients with JHD. Methods: The Kids' Inpatient Database (KID) was used to examine hospitalizations of children with JHD and to determine the diagnoses and procedures associated with inpatient care for JHD. Regression models were built to examine acute care outcomes, including death, length of stay, and disposition at discharge in patients with JHD compared with patients in the general KID data. Results: The proportion of JHD cases among hospitalized children was 1.23 per 100, 000 KID inpatient stays. Seizures/convulsions (58.5%) and psychiatric conditions (26.1%) were the most common primary or secondary diagnoses among JHD patient hospitalizations. The most common procedure was percutaneous endoscopic gastrostomy tube placement (8.6%). Compared with hospitalizations of the general population, hospitalizations of patients with JHD had a lower odds of discharge to home (adjusted odds ratio [AOR], 0.23; 95% confidence interval [CI], 0.14–0.37) and an increased likelihood of death (AOR, 8.03; 95% CI, 2.98–21.60) or discharge to a short‐term care facility (AOR, 4.44; 95% CI, 2.59–7.61). A diagnosis of JHD was associated with increased length of stay (7.04 vs. 3.75 days; P < 0.01). Conclusions: Children with JHD have unique acute care patterns. Future studies are needed to determine the extent to which coordinated care may impact inpatient and disposition needs.